STUDENTS PERCEPTION OF USING ZEP QUIZ IN ENGLISH LANGUAGE LEARNING AT THE TENTH GRADE OF SMAN 1 TANJUNGPINANG - Dea Aisyah Wulandari; Elsa Ernawati Nainggolan; Benni Satria (Journal Of Language Education and Development (JLed), 2026)
This study explores tenth-grade students' perceptions of using Zep Quiz in English language learning at SMAN 1 Tanjungpinang. A mixed-method approach was employed, involving 181 students who completed a 4-point Likert scale questionnaire and six purposively selected students who participated in semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings revealed that students generally held positive perceptions of Zep Quiz. Most participants perceived the platform as useful for improving vocabulary, grammar practice, and examination preparation through immediate feedback and repeated practice. Students also considered Zep Quiz easy to access and operate because of its simple interface and interactive features. Furthermore, the gamified elements, including leaderboards, avatars, and instant feedback, increased students’ engagement, motivation, and classroom participation. Although several technical and pedagogical challenges, such as unstable internet connections, login issues, limited material explanations, and time pressure, were identified, these obstacles did not substantially reduce students’ positive perceptions. Overall, Zep Quiz was perceived as an effective gamified learning platform that supports English language learning by promoting active participation, motivation, and meaningful learning experiences.